2008
DOI: 10.1063/1.2832780
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional features of the turbulent flow through a planar sudden expansion

Abstract: An experimental investigation of the turbulent flow downstream of a planar sudden expansion has been performed by means of a 2D particle image velocimetry ͑PIV͒ technique. Flow fields at the Reynolds number of 10 4 have been measured in several mutually perpendicular planes of a channel having an expansion ratio of 3 and an aspect ratio of 10. As usual for large expansion ratios, the separated flow exhibits a strong asymmetry about the expansion axis and, consequently, very different reattachment lengths on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…For the flow pattern A1 near the transition A1 -S0 ("short" reservoirs), when decreasing the water depth (but increasing the Froude number in the same time), Kantoush (2008) showed that the flow was not steady anymore but started to meander. For these fully turbulent flows, the influence of the Reynolds number is generally not significant (Abbott and Kline, 1962) but sometimes not completely negligible for the shorter reattachment length (Casarsa and Giannattasio, 2008 …”
Section: Introductionmentioning
confidence: 98%
“…For the flow pattern A1 near the transition A1 -S0 ("short" reservoirs), when decreasing the water depth (but increasing the Froude number in the same time), Kantoush (2008) showed that the flow was not steady anymore but started to meander. For these fully turbulent flows, the influence of the Reynolds number is generally not significant (Abbott and Kline, 1962) but sometimes not completely negligible for the shorter reattachment length (Casarsa and Giannattasio, 2008 …”
Section: Introductionmentioning
confidence: 98%
“…Such flows occur, for example, in pipes or fracture systems commonly encountered in chemical, pharmaceutical, petroleum and mining industries, or in geological repository of high‐level nuclear wastes and carbon sequestration (Bodvarsson et al , ; Wilson et al , ). Great efforts were put into the study for fluid flow through abruptly expanding pipes, plates, or fractures in the last several decades (Durst et al , ; Cherdron et al , ; Fearn et al , ; Casarsa and Giannattasio, ). An SF with an abruptly changing aperture (SF‐ACA) often has eddies or recirculation regions that result in longer residence time for water flow and solute transport.…”
Section: Introductionmentioning
confidence: 99%
“…Casarsa and Giannattasio (2008) showed that the effect of R on the shorter recirculation length is not completely negligible. As the present study only focuses fully turbulent flows, transitions from symmetric to asymmetric flows encountered at small R are not further considered (e.g.…”
Section: Froude Number F = U/(gh)mentioning
confidence: 99%